Monarch butterfiles - Rotter, Charles ([Mankato, MN] : Child's World ; Chicago, Ill. : Distributed to schools and libraries in the United States by Encyclopaedia Britannica Corp., 1993)
Introduces the physical characteristics, habits, and life cycle of the monarch butterfly.
Keywords: Monarch butterfly -- Juvenile literature; Monarch butterfly; Butterflies